Scaled Quantum FT-IR and FT-Raman Spectral Analysis of 1-Methoxynaphthalene. Issue 2 (2010) - Govindarajan, M.; Periandy, S.; Ganesan, K.
Abstract : The structural and vibrational property of 1-methoxynaphthalene has been studied. The fundamental vibrational frequencies and intensity of vibrational bands were evaluated using B3LYP/6-31G (d, p) basis set and was scaled using various scale factors, which yielded a good agreement between observed and calculated frequencies. The vibrational spectra were interpreted with the aid of normal coordinate analysis. The results of the calculations were applied to simulated spectra of the title compound, which shows excellent agreement with observed spectra. The calculated force constants in vibrational internal coordinates are in closely coincides with the experimentally observed force constants.